2020
DOI: 10.1002/cbdv.202000201
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilic Metabolites from Five‐Needle Pines, Pinus armandii and Pinus kwangtungensis, Exhibiting Antibacterial Activity

Abstract: Lipophilic extractive metabolites from needles and defoliated twigs of Pinus armandii and P. kwangtungensis were studied by GC/MS. Needles of P. armandii contained predominantly 15‐O‐functionalized labdane type acids (anticopalic acid), fatty acids, nonacosan‐10‐ol, sterols, nonacosan‐10‐ol and sterol saponifiable esters, and acylglycerols, while P. kwangtungensis needles contained no anticopalic acid, but more trinorlabdane (14,15,16‐trinor‐8(17)‐labdene‐13,19‐dioic acid) and other labdane type acids, nonacos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Comparing the results presented in our previous publications, which described the process of transformation of GA with the use of sepiolite (a mineral from the silicate group, classified as clay minerals) [ 29 ] and clinoptilolite (a mineral from the group of silicates, included in the group of zeolites) [ 30 ], with these described in this paper, it was observed that the previously tested catalysts required longer reaction time, a much higher catalyst content and higher temperature to obtain high values of selectivity of the transformation to the appropriate products and the conversion of GA. In general, the presented studies showed that increasing in the temperature or extending the reaction time causes a decrease in the value of the selectivity of the formation of compounds that most likely decompose because their structure is not stable.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Comparing the results presented in our previous publications, which described the process of transformation of GA with the use of sepiolite (a mineral from the silicate group, classified as clay minerals) [ 29 ] and clinoptilolite (a mineral from the group of silicates, included in the group of zeolites) [ 30 ], with these described in this paper, it was observed that the previously tested catalysts required longer reaction time, a much higher catalyst content and higher temperature to obtain high values of selectivity of the transformation to the appropriate products and the conversion of GA. In general, the presented studies showed that increasing in the temperature or extending the reaction time causes a decrease in the value of the selectivity of the formation of compounds that most likely decompose because their structure is not stable.…”
Section: Discussionmentioning
confidence: 94%
“…Thumbergol (one of the main products obtained in our work for studied in the presence of alum) is diterpene monocyclic alcohol used in cancer treatment This compound also shows neuroprotective [ 29 ] and antibacterial properties [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to COPA, little is known about the bioactivities of ACP . To date, there have only been reports of the antimicrobial activity of ACP 16 , 28 and antifeedant activity against Spodoptera frugiperda of ACP and derivatives 9 . In view of the limited existing studies of the bioactivities of ACP and the potential use of ACP in natural product-based drug discovery, we embarked on the synthesis and cytotoxic evaluation of ACP derivatives.…”
Section: Introductionmentioning
confidence: 99%